Mobile-based Tajwid 1 Learning Media at the Gontor Entrance Guidance Institution with the Demonstration Method - Muhammad Sirajuddin Mumtaz Dzaky; Dihin Muriyatmoko; Taufiqurrahman (Universitas Muhammadiyah Sidoarjo, 2021)
Darussalam Gontor Modern Boarding School (PMDG) graduates established tutoring institutions in their respective regions. The institution is called Bimbingan Masuk Gontor (Bimago). Currently, prospective students who want to enter Gontor have difficulty learning Tajwid 1 because of the limited learning media that still use printed books and the number is limited. This requires other media, one of which is a smartphone. The purpose of this research is to facilitate prospective students who want to learn the PMDG version of Tajweed 1. This study uses a Software Development Life Cycle approach and applies a demonstration method to its content. Application testing is done in 4 ways. With the blackbox method, it shows the application is running smoothly. The use of hardware with 5 smartphones of various brands and a screen size of at least 5.20 inches indicates the application is running well. A learning media expert gave an average of 94.38%. Six Tajwid teachers gave a score of 88.40%. The results of this study can be concluded that this application can help as an effective learning tool.